The therapeutic potential of Rho GTPase intervention - Friesland, Amy Michelle (East Carolina University, 2013)
Small GTPases of the Rho family are well established regulators of critical cellular functions including cytoskeletal remodeling, motility, vesicle trafficking and cell cycle control. Additionally, aberrant signaling and/or regulation of Rho proteins have been implicated in various human pathologies. For these reasons, there is increasing interest in Rho GTPases as targets for therapeutic intervention. In the current study, we aim to understand Rho GTPase involvement in neuronal degeneration associated with clinical cisplatin use. Using a mouse model of cisplatin-induced peripheral neuropathy (CIPN) and a primary neuronal culture system we investigated how RhoA pathway suppression concomitant with cisplatin could prevent neuronal damage. Additionally, in order to fill a large gap in the field of Rho GTPase study and to allow us to further understand Rho GTPase cross regulation, we sought to identify and characterize novel small-molecule inhibitors of the Rho family member Cdc42.   Using our CIPN mouse model, we examined RhoA pathway suppression with LM11A-31, a p75 neurotrophin receptor ligand mimetic, on both RhoA signaling and neuronal damage associated with cisplatin application. We determined that cisplatin-induced decreases in peripheral nerve sensitivity and abnormal peripheral nerve morphologies could be prevented with concurrent use of LM11A-31 and cisplatin. Additionally, cisplatin-induced increases in RhoA activity and expression could be inhibited by LM11A-31. Furthermore, in vivo and in vitro studies demonstrate that cisplatin can also reduce SHP2 phosphorylation, which in turn, can be alleviated by LM11A-31. These studies demonstrate the importance of RhoA signaling in the development of CIPN and highlight its usefulness as a potential therapeutic target.   To discover potential specific Cdc42 inhibitors, we applied high-throughput screening to identify compounds that are able to target the interaction between Cdc42 and its specific guanine nucleotide exchange factor, intersectin. ZCL278 was found to inhibit Cdc42 activity, expression, and directly bind to Cdc42. Additionally, ZCL278 inhibits Cdc42-mediated microspike formation, and disrupts GM130-docked Golgi structures. ZCL278 also suppresses Cdc42-mediated neuronal branching as well as cell motility and migration without disrupting cell viability. Therefore, ZCL278 is a novel small-molecule modulator of Cdc42 that will open the door to further study of Cdc42-mediated signaling pathways.
Keywords: Biology, Cellular; Biology; Chemistry, Biochemistry; Cdc42; Cisplatin; LM11A-31; RhoA; Rho GTPases; ZCL278; Cellular biology; Biochemistry; GTPase-Activating Proteins--therapeutic use; Arhgap10 protein, mouse; Models, Animal; Adaptor Proteins, Vesicular Transport